Motivasi dan Kesadaran Hidup Sehat Masyarakat Untuk Berolahraga Pada Masa New Normal di Kota Semarang (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to determine the motivation and awareness of healthy living in the community to exercise during the new normal in Semarang City. The population and sample in this study were the people of Semarang City who did sports activities during the new normal in the Simpang Lima area, Tri Lomba Juang, and the researchers' home environment. This research is included in quantitative descriptive research. The data collection technique used in this study was observation using a questionnaire. The data analysis method used in this research is descriptive percentage. The results showed that the people's motivation to exercise during the new normal period in Semarang City with a percentage score of 84.8%. This can be seen in the data tabulation that the average score for aspects of physiological needs is 83.5%, as much as 79.6% chose the time factor for exercise, as much as 84.6% chose sports activities, as much as 90% chose the environment and weather. The average score for the aspect of the need for safety was 87.3%, as many as 85.5% chose the factor of getting safety, as many as 87.9% chose the factor of feeling guaranteed health. The average score for the aspect of social needs was 82.2%, as much as 86% chose the factor of making new friends, as much as 86.2% chose the factor of wanting to exercise, as much as 83.5% chose the factor of social media needs. The average score for the aspect of the need for appreciation is 84%, as much as 82.7% choose the factor to improve skills, as much as 84.6% choose the factor to get success. The average score for aspects of self-actualization needs is 84.8%, as much as 82.2% choose the factor of developing sports activities, as much as 84.5% choose the sports target factor. For awareness of healthy life in the community in exercising during the new normal period in Semarang City, the percentage score is 89% with the data tabulation below the average score of maintaining fitness and immunity is 100%. The average score for maintaining cleanliness was 89.7%, as much as 90.7% chose factors according to health protocols, as many as 89.5% chose factors for body and environmental hygiene. The mean score for nutritious meals was 88.8%. The average rest or sleep score was 86.6%. The conclusion from the results of this study is that the people of Semarang City during the new normal period had very high motivation and awareness of healthy living to do sports activities.